Business Models in Fashion Area: A Study on Traditional and Innovative Sectors (ModaPalavra e-periódico, 2017)
The current highly competitive market leads companies to seek better performances, but also other forms of differentiation and organization. Assuming business model is how to organize strategic and operational details of the enterprise, in order to stand out in the market and separate the different sectors in which the industry covers, and fashion as one of the biggest industries in the market, we tried to establish the definition of different business models in this area, dividing them into two major groups: the traditional and the innovative. This research aims to point out some business sectors within the fashion, in a simplified and summarized form, serving as a basis for future works. The present study resulted from the lack of exploration of the area, in order to recognize and explore the operation of some business models.
Keywords: business models; innovation; creative economy